DNA fluorescence probes based on side-chain chlorinated benzo[a]phenoxazinium chlorides - Raju, B. Rama (2012)
Several side chain chlorinated benzo[a]phenoxazinium chlorides functionalized with various types of terminals at the 5- and 9-amino positions of the heteroaromatic ring were used in photophysical studies with DNA. It was found that the functionalised terminal has a dramatic influence on the type of interaction with the amino group at the 9-amino position greatly promoting intercalation.